Adolescent Emotional Pathology and Lifetime History of Alcohol or Drug Use With and Without Comorbid Tobacco Use. Issue 1 (2nd January 2016) - Chuang, Cheng-Wei I.; Chan, Connie; Leventhal, Adam M.
Abstract: Objective : Use of drugs and alcohol, including tobacco, is linked to adolescent emotional psychopathology. Given that tobacco use is becoming less common over recent years, its co-use with drugs/alcohol may mark a more severe profile of emotional symptomatology. However, it is unclear whether teens with a lifetime history of using drug/alcohol and tobacco exhibit additional elevations in emotional psychopathology and/or multiple forms of emotional psychopathology compared to teens with lifetime drug/alcohol use without comorbid tobacco use. This cross-sectional study compared emotional disorder symptoms and emotional vulnerability traits among adolescents with varying histories of substance use.Methods : Ninth-grade students enrolled at two schools in Los Angeles, California, were recruited; 575 met eligibility criteria and provided both student assent and parental consent. Students completed self-report measures of emotional pathology, transdiagnostic, and lifetime substance use. Participants were classified into three groupings: (a) no history of substance use ( n = 294); (b) lifetime history of drug/alcohol use without tobacco use ( n = 166); and (c) lifetime history of drug/alcohol use with concomitant tobacco use ( n = 115).Results : Chi-square results showed that teens with lifetime alcohol/drug use with (vs. without) comorbid tobacco use were more likely to have used 10 of 16 substances assessed in the study. Post-ANOVA pairwise tests revealed that, compared to students with no history of substance use, those with any history of use (alcohol/drugs with and without tobacco use) had higher major depression symptoms and negative affect. Those with lifetime alcohol/drug use with comorbid tobacco use had higher generalized anxiety symptoms and distress, and those with lifetime alcohol/drug use without comorbid tobacco use had higher panic disorder symptoms and anhedonia. There were no significant differences between adolescents with lifetime drug/alcohol use with comorbid tobacco use versus those without tobacco use.Conclusions : Adolescents with (vs. without) a lifetime history of drug/alcohol use endorse greater emotional symptomatology and trait vulnerabilities, regardless of comorbid lifetime tobacco use. Thus, the extent to which tobacco serves as a gateway to, correlate of, or consequence of other substance use may have little bearing on adolescent emotional health. This study's findings further suggest that emotional vulnerability (in addition to manifest psychopathology) should be considered in adolescent substance use and mental illness prevention.